2016
DOI: 10.1111/medu.12935
|View full text |Cite
|
Sign up to set email alerts
|

Is three a crowd? Impact of the presence of a medical student in the general practice consultation

Abstract: The presence of a medical student during the GP consultation was satisfactory for all participant groups. These findings support the ongoing and increased placement of medical students in regional general practice. Medical educators and GPs must recognise that patients may not raise personal issues with a student present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
3
0
6
Order By: Relevance
“…Ainda, estágios na APS oferecem aos alunos possibilidades de contatos diversas com pacientes, o que se torna um fator motivador para o aprendizado (SALMINEN et al, 2016;HAWTHORNE, DINH, 2017). Maximizar a exposição dos alunos à APS é importante para que países orientados à atenção primária possam atingir melhores níveis de saúde e maior satisfação com relação aos serviços de saúde pela população (PARTANEN et al, 2016).…”
Section: -O Contexto De Realização Do Estágio Curricular Em Medicinaunclassified
See 1 more Smart Citation
“…Ainda, estágios na APS oferecem aos alunos possibilidades de contatos diversas com pacientes, o que se torna um fator motivador para o aprendizado (SALMINEN et al, 2016;HAWTHORNE, DINH, 2017). Maximizar a exposição dos alunos à APS é importante para que países orientados à atenção primária possam atingir melhores níveis de saúde e maior satisfação com relação aos serviços de saúde pela população (PARTANEN et al, 2016).…”
Section: -O Contexto De Realização Do Estágio Curricular Em Medicinaunclassified
“…Muitos pacientes acreditam que possuem um papel importante no aprendizado dos alunos, especialmente em um contexto de cuidado centrado no usuário (PARTANEN et al, 2016). Nessa perspectiva, estudo desenvolvido na Austrália apresentou como objetivo explorar no contexto rural: a. experiências dos pacientes e satisfação com a consulta, b. a satisfação dos médicos generalistas com sua habilidade de conduzir a consulta de forma efetiva, envolvendo alunos e c. a perspectiva dos alunos sobre oimpacto da sua presença e o processo de aprendizado(PARTANEN et al, 2016). Há um aumento de estudos publicados descrevendo o ensino médico rural como parte de uma estratégia para lidar com a ausência de médicos em clínicas rurais(BARTLETT et al, 2016).…”
unclassified
“…The research that exists showed the relationship between patients and learners to be positive 36. Recent data in the primary care literature suggested that patients were satisfied with encounters where medical learners are involved, but patients were less inclined to share sensitive or personal issues with their personal physicians when medical learners are present 7…”
Section: Introductionmentioning
confidence: 99%
“…Research in the medical student context, finds that teaching and learning in general practice consultations is generally a positive and valuable experience for all three participants: the patient, the student and the general practitioner . Importantly, studies have shown no negative impact on patients when comparing teaching and non‐teaching consultations . Additionally, many patients believe they play an important role in the learning experience of trainees and that teaching during the consultation enhances the quality of their care .…”
mentioning
confidence: 99%
“…Importantly, studies have shown no negative impact on patients when comparing teaching and non‐teaching consultations . Additionally, many patients believe they play an important role in the learning experience of trainees and that teaching during the consultation enhances the quality of their care . Patients indeed are at the centre of medical education and clinicians, whether novice or experienced, continue to learn from their patients.…”
mentioning
confidence: 99%